2008
DOI: 10.20450/mjcce.2008.230
|View full text |Cite
|
Sign up to set email alerts
|

A novel environmentally friendly 2,4,6-trinitrotoluene (TNT) based explosive

Abstract: A novel bioremediation technology has been developed. This technology involves the incorporation of a newly isolated Pseudomonas putida GG04 and Bacillus sp. SF into an explosive formulation to enhance biodegradation of TNT residues and explosives which fail to detonate due to technical problems. The incorporation of these microorganisms into the explosive did not affect the quality of the explosive in terms of detonation velocity while complete degradation of TNT moieties upon transfer in liquid media was obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
1
0
3
Order By: Relevance
“…cereus transformed TNT to 2,4-dinitrotoluene and 4-aminodinitrotoluene derivates and degraded 77% of 75 mg L −1 , TNT within 96 h (Mercimek et al, 2013 ). Nyanhongo et al ( 2008 ) reported that Bacillus sp. SF transformed TNT via an initial reduction mechanism to produce hydroxylaminodinitrotoluenes, 4-amino-2,6-dinitrotoluenes, 2-amino-4,6-dinitrotoluenes, different azoxy compounds, 2,6-diaminonitrotoluenes, and 2,4-diaminonitrotoluenes.…”
Section: Role Of Bacillus Species In Biodegradatiomentioning
confidence: 99%
“…cereus transformed TNT to 2,4-dinitrotoluene and 4-aminodinitrotoluene derivates and degraded 77% of 75 mg L −1 , TNT within 96 h (Mercimek et al, 2013 ). Nyanhongo et al ( 2008 ) reported that Bacillus sp. SF transformed TNT via an initial reduction mechanism to produce hydroxylaminodinitrotoluenes, 4-amino-2,6-dinitrotoluenes, 2-amino-4,6-dinitrotoluenes, different azoxy compounds, 2,6-diaminonitrotoluenes, and 2,4-diaminonitrotoluenes.…”
Section: Role Of Bacillus Species In Biodegradatiomentioning
confidence: 99%
“…biol. 20(2): 145 -150 (Diciembre 2013) asegurada por sus características químicas, por lo que algunos dispositivos explosivos en la industria minera o petrolera pueden no explosionar por problemas técnicos y constituirse en un riesgo para el ambiente y las personas (Nyanhongo et al 2008).…”
Section: Introductionunclassified
“…En los resultados de transformación y recuento se presentaron casos en donde se observa una transformación de TNT, pero no de PETN (y viceversa), transformación de alguno de los dos explosivos, sin recuento (o viceversa) y la ausencia de transformación y recuento. En los ensayos de transformación de TNT y PETN adelantados dentro de este estudio (Avila-Arias et al, 2017;Ávila, 2012;García, 2014) y en ensayos de transformación del explosivo sólido (TNT) (Erkelens et al, 2012;Nyanhongo et al, 2008) siempre hay un crecimiento asociado a la transformación de los explosivos. En estos ensayos también se observaron precipitados de colores (amarillo-rojo) en el medio (Erkelens et al, 2012;Nyanhongo et al, 2009) la producción de estos colores también se ha observado en la hidrolisis del TNT, aunque en condiciones de pH alcalinos (11-12) (Hwang et al, 2005).…”
Section: Monitoreo De La Transformación De Pentolita Sólidaunclassified
“…Lo que es desconcertante. No existen muchos estudios sobre la transformación de explosivos en forma sólida, Erkelens y colaboradores (Erkelens et al, 2012) obtuvo transformaciones mucho más altas (70%) utilizando bacterias provenientes de suelos contaminados con hidrocarburos, Nyanhongo y colaboradores (Nyanhongo et al, 2008(Nyanhongo et al, ,2009 desarrollaron un explosivo biodegradable basado en TNT, con bacterias aisladas de un sitio contaminado por TNT.…”
Section: Monitoreo De La Transformación De Pentolita Sólidaunclassified